Chapter Altre rivolte. Violenza antisignorile nell'Italia tardomedievale - GRAVELA, Marta (Reti Medievali E-Book, 2023)
Peasant revolts were widespread in late medieval Europe. Based on the extensive investigation of the project La signoria rurale nell'Italia del tardo medioevo, this essay examines the numerous cases of peasant rebellion in the Italian peninsula, scarcely known to historians - who have mostly focused on urban uprisings - and never assessed on a large scale. The comparative perspective allows to analyse the causes, contexts, relevance, and results of such revolts, as well as to understand not only the features of lordships in late medieval Italy, but also the nature of the relationship between lords and subjects.